Potential for donation after circulatory death heart transplantation in the United States: Retrospective analysis of a limited UNOS dataset. Issue 2 (28th October 2019) - Farr, Maryjane; Truby, Lauren K.; Lindower, Joel; Jorde, Ulrich; Taylor, Samantha; Chen, Leway; Gass, Alan; Stevens, Gerin; Reyentovich, Alex; Mancini, Donna; Arcasoy, Selim; Delair, Samantha; et al.
Abstract : Donation after Circulatory Death (DCD) is an alternative to Donation after Brain death (DBD), and is a growing strategy for organ procurement in the United States(US). The purpose of this analysis was to review the number and quality of hearts in one United Network for Organ Sharing (UNOS) Region that were not utilized as a potential consequence of nonheart DCD donation. We retrospectively identified all successful US DCD solid organ donors from 1/2011 to 3/1/2017, defined an ideal heart donor by age and left ventricular ejection fraction (LVEF), and then reviewed the donor charts of unused hearts in New York and Vermont (UNOS Region 9). Of 8302 successful DCD donors across the United States, 5033 (61%) were between 18 and 49 years of age, and 872 had a screening echocardiogram, with 573 (66%) measuring an EF >50%. Of these 573 potential donors, 44 (7.7%) were from Region 9. Detailed donor chart review identified 36 ideal heart donors, 24 (66.7%) with anoxic brain injury. Trends in Region 9 DCD donation increased from 4 unused hearts in 2011, to 13 in 2016. In the context of severe organ scarcity, these data indicate that implementation of DCD heart transplantation in the United States would improve overall donation rates and provide a pathway to utilize these ideal donor hearts. Abstract : A retrospective analysis of a UNOS dataset identifies a growing cohort of unused donor hearts because of donation after circulatory death procurement and lack of current algorithms for heart transplantation in this setting.